Study of the virulence factors and antimicrobial susceptibility profile of staphylococcus aureus isolated from clinical samples at tertiary care centre - Dr.Vedavati B. I.; Dr. Halesh L.H.; Dr. Mallikarjun Koppad; Dr. D. E. Premalatha; Dr. Akshatha Y.J. (Tropical Journal of Pathology and Microbiology, 2019)
Introduction: Staphylococcus aureusis an important cause of healthcare-associated infections. The increasing resistance of this pathogen to various antibiotics complicates treatment. Present study was conducted to isolate staphylococcus aureus from various clinical samples, to study the few virulence factors, antibiogram and to detect methicillin resistance among them. Materials and Methods: Present study was done over a period of six months. The study was conducted on 100 staphylococcus aureus isolated from various clinical samples. The organisms were identified as per standard conventional methods. The antibiotic sensitivity testing of the isolates was done by Kirby Bauer’s Disk Diffusion method according to CLSI guidelines. These strains were screened for DNase production, beta hemolytic property and slime production. Results: Among 100 clinical isolates of staphylococcus aureus 82% of them showed beta hemolysis, 79% produces DNase, 72% produces slime. The proportion of MRSA amongst S. aureus isolates was found to be 53%. MSSA were 100% sensitive to vancomycin and linezolid85.10 % to Doxycycline, 82.98% to clindamycin, 72.34% to chloramphenicol, 68.09% Co- trimoxozole, 65.95% to erythromycin, 61.70% gentamicin, 51.06 % to Ciprofloxacin, 12.77% topenicillin. MRSA were 100% sensitive to vancomycin and linezolid, 71.69% Doxycycline, 64.15% to Chloramphenicol, 60.37% to Clindamycin, 43.39% to Ciprofloxacin, 39.62% Gentamicin, 37.74% Co- trimoxozole, 35.84% to Erythromycin and all the isolates were resistant to penicillin. Conclusion: Understanding of virulence mechanisms and antibiotic susceptibility pattern of Staphylococcus aureus is important for effective management of infections.